The contrasting roles of aquatic fungi and oomycetes in the degradation and transformation of polymeric organic matter. (16th July 2019) - Masigol, Hossein; Khodaparast, Seyed Akbar; Woodhouse, Jason Nicholas; Rojas‐Jimenez, Keilor; Fonvielle, Jeremy; Rezakhani, Forough; Mostowfizadeh‐Ghalamfarsa, Reza; Neubauer, Darshan; Goldhammer, Tobias; Grossart, Hans‐Peter
Abstract: Studies on the ecological role of fungi and, to a lesser extent, oomycetes, are receiving increasing attention, mainly due to their participation in the cycling of organic matter in aquatic ecosystems. To unravel their importance in humification processes, we isolated several strains of fungi and oomycetes from Anzali lagoon, Iran. We then performed taxonomic characterization by morphological and molecular methods, analyzed the ability to degrade several polymeric substrates, performed metabolic fingerprinting with Ecoplates, and determined the degradation of humic substances (HS) using liquid chromatography‐organic carbon detection. Our analyses highlighted the capacity of aquatic fungi to better degrade a plethora of organic molecules, including complex polymers. Specifically, we were able to demonstrate not only the utilization of these complex polymers, but also the role of fungi in the production of HS. In contrast, oomycetes, despite some morphological and physiological similarities with aquatic fungi, exhibited a propensity toward opportunism, quickly benefitting from the availability of small organic molecules, while exhibiting sensitivity toward more complex polymers. Despite their contrasting roles, our study highlights the importance of both oomycetes and fungi in aquatic organic matter transformation and cycling with potential implications for the global carbon cycle.